(NnAPRAWLENIE MODY W ODEVDE I TKANQH NA (B1961-1961 (NGOD (B.s ((NmOSKWA (B:s [(NB(B. (NI(B.],s, 1960)
(NpRILOVENIE K KATALOGU oB]ESO@ZNOJ WYSTAWKI TEKSTILXNYH TOWAROWs
Keywords: (NoDEVDAs; (N{WEJNAQ PROMY[LENNOSTXs